The impact of relationship between working capital management and firm's profitability : evidence from firms listed in Bursa Malaysia / Dora Sakai - Sakai, Dora (2017)
Since Working capital is to manage the operations both maturing short-term debt and upcoming operational expenses, it has a huge impact on profitability of firms. Working capital involves in managing inventories, cash and account receivables and payables. In this study it aims to revealing the relationship of working capital towards profitability of companies in Malaysia. Since there are very limited data can be gathered in the specific sector, this study will select any sector in Malaysia except financial sectors because the data is not capable of gathering for this study. The variable that has been used is gross operating profit as dependent variables, while the independent variables are cash conversion cycle and inventory holding turnover. The data are collected based on 30 companies which are listed on Bursa Malaysia for the period 2011 until 2015 which is 5 years.